(untitled) (Singaporean Journal of Business Economics and Management, 2013)
This paper investigates the nature and behaviour in Shariah market of GCC countries with daily returns spanning from 01/12/2008 to 31/08/2013. In order to model the volatility, GARCH (1, 1), E- GARCH (1, 1) and T-GARCH (1, 1) have been employed. After detecting the ARCH effect, the residuals were modelled with the above tools. The results of GARCH (1, 1) were highly significant at 1% significance level. The high significance of a (ARCH term) and ẞ (GARCH term) implies that past volatility highly influences the current volatility of all the series under study. The asymmetrical GARCH models outperformed the symmetrical GARCH models. By the application of E-GARCH (1, 1) and T-GARCH (1, 1) it was found that that there was leverage effect in the all the indices with few exceptions. The results of T-GARCH (1, 1) showed that there was no asymmetry in the returns of Bahrain and Oman when compared to all other indices. With regard to E-GARCH (1, 1) results it was witnessed that Bahrain, Saudi Arabia, Qatar and United Arab Emirates were highly significant at 1% level with negative coefficients of leverage effect indicating that negative news highly influences the market than positive news, but Kuwait and Oman were the exceptions in the conditional modelling. In both the cases Oman stood out with a negative result. The results of the study provides insight in to volatility structure of Shariah markets more specifically the indices of GCC countries, which is of great help for the investors in Shariah index of GCC countries.